PENGAWASAN PELAKSANAAN TUGAS VILLA ATTENDANT DI BANYAN TREE BINTAN RESORT - Emia Rehjorena br Sihite; Teguh Widodo (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
Implementation instructions are corrective actions in carrying out the tasks in accordance with predetermined plans, instructions and instructions, so that the objectives that have been provided can be obtained. It is important to supervise the company to be in accordance with the standards set by the company. but in addition to improvement, the banyan tree also provides feedback and also provides feedback to employees for good work during the work. This study discusses (1) to learn how to oversee the implementation of villa staff duties at Banyan tree Bintan Resort (2) and explore what are under supervision of the implementation of villa maid duties at Banyan Bintan Resort. This study uses a qualitative method by discussing descriptive, research subjects are supervisors of Banyan Tree Bintan Resort. Data collection is done is the collection, documentation, interviews. The villa clerk at Banyan Tree Bintan Resort in supervising his subordinates using standard operating procedures (SOP). Bosses in carrying out their duties Bosses carry out their duties very well in the results of interviews and meeting results based on guest satisfaction and the room occupancy rate is quite good. discuss housekeeping supervisors at the Villa Attendant supervision at the Banyan Tree Bintan resort, select employees in the Villa Attendant section, choose transportation used to allow villa officials, postpone Stock items that have not arrived at the hotel from Thai shipments to Bintan Key Informan: performance of duty